Whole-body vibration exposure of Malaysian taxi drivers - A. R. Ismail; S. N A Abdullah; A. A. Abdullah; B. M. Deros (2015)
During their whole working time, taxi drivers are usually seated. Additionally, long-term exposure to whole-body vibration while driving may lead to diseases and adverse health conditions such as lower-back pain. The objective of this study is to investigate the relationship between measurable whole-body vibration and lower-back pain. This study was conducted on two highways: Kuala Lumpur-Karak Highway and the North-South Highway. A tri-axial seat accelerometer was placed at the point of contact between the driver and the seat pad. The assessment of whole-body vibration measurement is according to ISO 2631-1. Excessive whole-body vibration has been evidenced as leading to lower-back pain. Taxi drivers are recommended to drive no more than the allowable exposure limit. In this study, the whole-body vibration does not exceed the allowable exposure limit. Therefore, the taxi drivers in this study do not have lower back pain.